Who knows better in an Emerging Market? Performance of Institutions, Foreigners and Individuals. (2015)
We find that local investors do better than foreigners in terms of trading execution. However foreign investors obtain better returns than local individuals both in short and long term. Local institutions are the best group on both dimensions. Our result reconcile apparent contradictions in the international finance literature on who invests better in an emerging market. These contradictions disappears with a more careful formulation of the research question at hand. The traditional Locals vs Foreigners or Institutions versus Individuals is too simplistic because it doesn’t distinguish between the different dimensions of performance. Our study makes use of two unique databases of Colombian stocks and acts as out-of-sample test of previous findings. Moreover, we provide evidence that the better performance of Institutions and Foreigners is driven by information advantages.